Eyewear : a visual history 1491-today - Lipow, Moss (Köln : Taschen, 2011)
Eyeglass designer Moss Lipow trawled eBay, auction houses, garage sales, and flea markets worldwide to amass glasses and photographs for his massive eyewear collection. This book, which traces eyewear{u2019}s journey over the past millennium, features the best examples from Lipow{u2019}s collection as well as models from other world class collections. Considering the wealth of examples included herein{u2013}such as prehistoric whalebone eye guards used by Eskimos, 13th century wooden rivet spectacles for Italian clergy, Medieval strap-on leather goggles, lorgnettes worn by 19th century dandies, pince-nez and monocles, early 20th century aviator sunglasses, and Godard{u2019}s mod plastic frames{u2013}it{u2019}s abundantly clear that eyewear has experienced a surprising and fascinating evolution; what was once a purely practical apparatus has grown into a multi-billion dollar global industry catering to both the visually impaired and the fashionably inclined. Accompanying the wealth of images in this wide-ranging volume are insightful texts informed by a wide variety of sources including ancient texts, old catalogues, vintage magazines, and out-of-print publications of every kind
boek
Keywords: Brillen -- geschiedenis